A STUDY ON THE EFFECT OF SITUATIONAL LEADERSHIP ON JOB SATISFACTION AMONG HEALTHCARE EMPLOYEES - Anna Najieva Basir Bantuas; Madelle Conales, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Given the pandemic and the emergence of a new normal, healthcare has become a top priority. Consequently, it is crucial to examine both the individuals and the organizational governance of healthcare entities to ensure their sustainability. This study investigates the influence of situational leadership on job satisfaction in the healthcare sector, specifically within a medical center in Lanao del Sur province. The research employs a quantitative design, utilizing a structured questionnaire to gather data from a sample of 110 respondents selected through quota sampling among the hospital’s permanent employees. This sample includes participants from key divisions such as Medical Services, Nursing, Finance, and Administrative Services, ensuring diverse representation. The findings reveal a moderately positive correlation between situational leadership practices and job satisfaction, suggesting that adaptable leadership styles significantly contribute to enhancing job satisfaction among healthcare staff. These results underscore the importance of effective leadership in fostering a supportive work environment, providing valuable insights for organizations aiming to improve employee well-being and performance.